CRATAEGUS L. ТУЎЫСЫ ТҮРЛЕРИНИҢ БИОЭКОЛОГИЯСЫ ҲӘМ ХОЖАЛЫҚ ӘҲМИЙЕТИ - Отенова, Ф.Т.; Нурмахашева, Г.С. (FAN va JAMIYAT, 2018)
The article deals with the history of introduction of Crataegus L. in Karakalpakstan, its bioecological peculiarities as well as its role in agriculture.